LEARNING SPEAKING STRATEGIES IN PERSONAL EXPERIENCES: A NARRATIVE INQUIRY - Mukhammad Wakhid Qomari (Graduate Program, University of Islam Malang, 2021)
This research is aimed to (1) explain what experiences of learning English speaking have been important to the participant; (2) to explain how the experiences construct the participant’s Speaking Skills in EFL context; and (3) to explain what can be learnt from the experiences of this learning English speaking. To conduct this research, the researcher use narrative inquiry, to understand the lived experience of an individual. A participant, named Karjo (pseudonym), participates in this research. He is willing to re-tell his lived experiences as studying at an English course institution in Pare, Kediri, East Java. To collect the data, the researcher uses semi structured (open-ended questions) interview. The data gathered, then, are analized through Clandinin and Huber (2010) way.The results show that, firstly, there are some of the participant’s experiences that are important in constructing his understanding about learning speaking strategies. The second, it is found that the participant used some strategies proposed by Oxford (1990) in learning speaking skills. The startegies include direct and indirect strategies. Direct strategies which are used by the participant are memory, cognitive and compensation strategies. Then, indirect strategies which he used are affective and social strategies. Key Words: language learning strategies, speaking, narrative inquiry